Kekangan guru menerapkan kemahiran berfikir dalam mata pelajaran teknik dan vokasional - Oman, Noor Liza (2013)
This study was conducted to explore the constraints faced by teachers in implementing thinking skills in technical and vocational subjects. A total of five research questions had been created for this study based on constraints related to teacher, student, resource, curriculum and environment. This study involved 137 teachers who are teaching technical and vocational subjects in four technical and vocational schools in the Johor Bahru district. This study employed quantitative method. A set of questionnaire was used as the instrument of the study. Reliability value Cornbrash’s Alpha= 0.86 shows that the entire questionnaire items are reliable. The data were analysed by using Statistical Package for Social Science (SPSS) software to obtain the mean value. The findings revealed that teacher-related constraints were the major barrier in applying thinking skills. Some suggestions to overcome the constraints in applying thinking skills are also being discussed. This study can be a guide for relevant parties to identify teachers’ constraints in applying thinking skills in technical and vocational subjects hence action to overcome the constraints can be taken